Self-reported task-oriented physical activity: A comparison with objective daily step count in COPD. (July 2018) - Wan, Emily S.; Kantorowski, Ana; Homsy, Diana; Kadri, Reema; Richardson, Caroline R.; Mori, DeAnna; Moy, Marilyn L.
Abstract: Background: Low physical activity (PA) is associated with adverse health outcomes independent of airflow limitation in COPD. Self-reported assessments are often limited to global estimates of PA and may not be directly translatable to patients' goals and motivations. We developed a task-oriented PA checklist and examined its performance relative to pedometer-assessed daily step count in two COPD cohorts. Methods: Task-oriented daily physical activity (DPA) was assessed in two COPD cohorts using either interviewer-administered recall questionnaire (DPA-R, Cohort 1, n = 109) or a self-administered diary-format daily checklist (DPA-C, Cohort 2, n = 175). Daily step count was measured in both cohorts using the Omron HJ-720 ITC pedometer. Univariate associations between individual DPA items and [a] cross-sectional and [b] longitudinal change (Cohort 1) in daily step count were assessed using a Pearson's correlation. Composite scores comprised of individual DPA items with univariate association p-values <0.1 were tested for association with daily step count using multivariate models. Results: Tasks associated with average daily step count in both cohorts included putting on shoes, showering, washing hair, walking for exercise, the frequency of walks >10 min, and walking on an incline (Pearson's rho range = 0.14–0.43). A composite score of these 6 DPA items demonstrated significant associations with baseline average daily step count in both cohorts (ρ = 0.5 & 0.47, Cohorts 1 & 2, respectively) and longitudinal change in daily step count (ρ = 0.46, Cohort 1). Conclusions: Self-reported task-oriented assessments complement direct monitoring and have potential clinical utility in exercise counseling to increase PA among COPD patients. Trial registration: ClinicalTrials.gov NCT01772082. Highlights: Task-oriented questionnaires & checklists correlate with physical activity in COPD. Composite scores correlate with baseline step count in 2 independent COPD cohorts. A 6-item composite score correlates with change in step count over 3 months.